The prevalence and possible risk factors of internet gaming disorder among adolescents and young adults: Systematic reviews and meta-analyses - Gao, Yuan-Xia; Wang, Jiang-Yang; Dong, Guang-Heng (Journal of psychiatric research, 2022)
As a spreading addictive behaviour in recent years, internet gaming disorder (IGD) has been studied a lot and the overall research results indicate that IGD has a high prevalence among adolescents and young adults (AYAs). To update the status quo of prevalence, it is necessary to conduct comprehensive analyses. On the premise of following the PRISMA statement, the study conducted two systematic reviews and meta-analyses to assess the global prevalence of IGD among AYAs and identify its possible risk factors. To achieve the goals, PubMed and CNKI databases were used to select the concerned studies published up to May 31, 2021. Heterogeneity was assessed using a funnel plot, Begg's test, Egger's test, and trim-and-fil method, followed by sensitivity analysis, subgroup analysis, and meta-regression analysis. For the meta-analysis of prevalence, 407,620 participants from 155 reports in 33 countries were included. The pooled prevalence of IGD among AYAs was 9.9% (95% CI: 8.6%–11.3%, P = 0.000, I2 = 94.4%), including 8.8% (95% CI: 7.5%–10.0%) among adolescents and 10.4% (95% CI: 8.8%–11.9%) among young adults. The following 12 factors are the possible risk factors of IGD among AYAs, which are stress, long average game time, family dysfunction, poor academic performance, being bullied, bullying, interpersonal problems, hyperactivity/inattention, anxiety, depression, emotional distress and low self-esteem. This study confirms the prevalence and possible risk factors for IGD among AYAs. It's valuable in understanding the threat of IGD and finding intervention strategies for IGD among AYAs. •Provides updated global prevalence of internet gaming disorder among adolescents and young adults in summary (9.9%) and separately (8.8% vs 10.4%).•Higher prevalence of internet gaming disorder among adolescents and young adults in males (15.4%) compared to females (6.4%).•Identify 12 possible risk factors for internet gaming disorder among adolescents and young adults.